Event studies in international finance research - El Ghoul, Sadok; Guedhami, Omrane; Mansi, Sattar A.; Sy, Oumar (Journal of International Business Studies, 2023)
Event studies are widely used in finance research to investigate the implications of announcements of corporate initiatives, regulatory changes, or macroeconomic shocks on stock prices. These studies are often used in a single-country setting (usually the U.S.), but little work has yet been conducted in an international context, perhaps due to the complexities inherent in implementing cross-country studies. This paper explores the methodological challenges of conducting event studies in international finance research. We emphasize how scholars should choose an event, select the study period (short vs. long term), estimate abnormal returns, infer statistically whether the event under consideration produces a reliable price reaction, and explore the role of formal and informal institutions in explaining cross-country differences in price reactions. We also provide an extension of event studies to an important but less studied asset class in an international setting – the fixed-income market. We conclude by offering practical recommendations for researchers conducting cross-country finance event studies and identifying opportunities for future research. Given the increasing number of global events, such as the COVID-19 pandemic, Brexit, and the Paris and Trans-Pacific Partnership agreements, we believe our paper is especially timely.